2003
DOI: 10.1038/sj.bjc.6600728
|View full text |Cite
|
Sign up to set email alerts
|

IGF1 genotype, mean plasma level and breast cancer risk in the Hawaii/Los Angeles multiethnic cohort

Abstract: The insulin-like growth factor 1 gene (IGF1) is a strong candidate gene for a breast cancer susceptibility model. We investigated a dinucleotide repeat 969 bp upstream from the transcription start site of the IGF1 gene for possible associations with plasma IGF1 levels and breast cancer risk in a multiethnic group of postmenopausal women. Furthermore, we investigated the relation between race/ethnicity, mean plasma IGF1 levels and breast cancer rates in the Hawaii/Los Angeles Multiethnic Cohort. The mean ageadj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
71
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 9 publications
12
71
0
Order By: Relevance
“…We chose to genotype non-carriers from the same families as the women participating in the study, because these women belong to the same ethnic and socioeconomic background and live in the same geographic area as the participants and are thus optimal controls. Others have reported similar frequencies for the absence of the 19-repeat allele among Caucasians ranging between 6.4 and 11.6% (Vaessen et al, 2001;DeLellis et al, 2003). The absence of the IGF1 19-repeat allele was found at a higher frequency among known BRCA1 mutation carriers (30%) compared with other women (11.5%) in the present study.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…We chose to genotype non-carriers from the same families as the women participating in the study, because these women belong to the same ethnic and socioeconomic background and live in the same geographic area as the participants and are thus optimal controls. Others have reported similar frequencies for the absence of the 19-repeat allele among Caucasians ranging between 6.4 and 11.6% (Vaessen et al, 2001;DeLellis et al, 2003). The absence of the IGF1 19-repeat allele was found at a higher frequency among known BRCA1 mutation carriers (30%) compared with other women (11.5%) in the present study.…”
Section: Discussionsupporting
confidence: 79%
“…The box length is the interquartile range. the absence of the 19-repeat allele varies greatly between ethnic groups and is highest among African-American women (Jernström et al, 2001a;DeLellis et al, 2003). Missmer et al (2002) found no interaction between the absence of the 19-repeat allele and overall breast cancer risk.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have not typed a CA repeat polymorphism located in the 5 0 region of IGF1, between SNPs rs35767 and rs2162679, which has been frequently included in previous studies. Several epidemiological studies on the association between this polymorphism and breast cancer risk or IGF-I levels (Jernstrom et al, 2001a;Yu et al, 2001;Figer et al, 2002;Missmer et al, 2002;DeLellis et al, 2003) have yielded highly conflicting results. This microsatellite polymorphism has a large number of alleles, which results in fractioning the study population into a large number of classes.…”
Section: Discussionmentioning
confidence: 99%